Working guide to drilling equipment and operations - Lyons, William C. (Gulf Pub./Elsevier, 2010)
Drilling technology has evolved in order to get at the increasingly harder to find oil, and in a more environmentally friendly way. Successful drilling operations require blending many technologies. Drilling equipment and procedures have a unique language that must be conquered in order to understand drilling operations. Working Guide to Drilling Equipment and Operations provides a fundamental, basic knowledge of the intricacies of drilling fluid, drilled solids management, drill bits, drill string design, directional drilling, cementing, casing, hydraulic optimization, and a discus.
Keywords: Oil well drilling -- Equipment and supplies.; Gas well drilling -- Equipment and supplies.; Oil well drilling rigs.; elektronické knihy; electronic books